Endodontic Management of Aberrant Root Canal Anatomy in Premolars - A Report of Two Cases - Nidambur Vasudev Ballal; Himanshu Jain (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
Premolars are recognized for their aberrant root canal anatomy. The unique feature of dilacerations and multiple root canals pose utmost challenge in the endodontic management. A clinician is required to have an insight of the morphology of tooth related to its shape, form and structure prior to commencing root canal treatment. This article describes the endodontic management of two cases of aberrant root canal anatomy in premolars.